Quarteto Ao Cair da Tarde (1981) para violinos, de Ernst Mahle: estratégias técnico-interpretativas para a construção de uma performance - Rafael Ribeiro (2020)
We present here a technical-interpretative analysis of the Quarteto Ao Cair da Tarde (1981) for violins by the German composer naturalized Brazilian, Ernst Mahle. Considering the work as a reference didactic material, we propose technical and interpretative strategies which include bow drawing, vibrato, fingering, dynamics, articulation and possible phrasing, aiming to construct a performance.